2020
DOI: 10.28991/hef-2020-01-04-04
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Variety and Nitrogen Levels on the Performance of Pearl Millet: Pennisetum Glaucum (L.) R. BR.

Abstract: The trials were conducted in 2010 and 2011 rainy seasons at Usmanu Danfodiyo University, Sokoto Teaching and Research Dry Land Farm, Dundaye, Nigeria to determine the effects of variety and nitrogen levels on performance of  (SOSAT c-88 and Zango millet varieties). Data collected were on Stand count, tiller count, plant height and panicle length. Others included panicle weight and grain yield. All data collected were subjected to analysis of variance (ANOVA). The results SOSAT c-88 and Zango millet indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…Additional evidence for the potential benefits of delaying the planting date has on millet yield in Senegal can be seen in other studies, thus confirming our results (Araya et al, 2022;Vieira Junior et al, 2023). Finally, other studies in Senegal on the use of N fertilizer for millet found the range of the best fertilizer rates to go from 68 kg N ha −1 to 120 kg ha −1 (Araya et al, 2022;Bastos et al, 2022;Isah et al, 2020;Vieira Junior et al, 2023), which is in agreement with our results. for the alternative agricultural scenarios after running the FARMSIM simulations.…”
Section: Overall Summarysupporting
confidence: 93%
“…Additional evidence for the potential benefits of delaying the planting date has on millet yield in Senegal can be seen in other studies, thus confirming our results (Araya et al, 2022;Vieira Junior et al, 2023). Finally, other studies in Senegal on the use of N fertilizer for millet found the range of the best fertilizer rates to go from 68 kg N ha −1 to 120 kg ha −1 (Araya et al, 2022;Bastos et al, 2022;Isah et al, 2020;Vieira Junior et al, 2023), which is in agreement with our results. for the alternative agricultural scenarios after running the FARMSIM simulations.…”
Section: Overall Summarysupporting
confidence: 93%
“…The application of nitrogen fertilizer at the appropriate time improves numerous physiological processes involving photosynthesis, root growth and development, and elongation of structural tissues such as the stalk in cereals. Similar findings were reported by Isah et al [11].…”
Section: Panicle Length (Cm)supporting
confidence: 92%
“…In addition, analyses of the chemical composition of these litters showed significantly higher concentrations of P and K in coir-husk fiber, essential components along with N in agricultural fertilization, in particular in food and biofuel crop production. On the other hand, tropical soils tend to be poor in N, P and K (Isah et al, 2020 ). Thus indicating that after use as poultry litter, this material can be composted and used as a natural fertilizer in agriculture (Frazão et al, 2021 ), once again promoting sustainability and making production cheaper, since Brazil has large agricultural areas, being one of world’s leading producers and suppliers of food, fibers and bioenergy (Fao, 2017 ) and is highly dependent on imported fertilizers, mainly from Russia, which makes this research highly important for the Brazilian agricultural sector.…”
Section: Introductionmentioning
confidence: 99%